2019
DOI: 10.1097/md.0000000000015773
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of tumor necrosis factor in the blood serum and in the urine and selected early organ damages in patients with primary systemic arterial hypertension

Abstract: Arterial hypertension is considered to be an inflammatory condition with low intensity. Therefore, an elevated concentration of inflammatory cytokines can be expected in patients with systemic arterial hypertension, including tumor necrosis factor (TNF). The study included a group of 96 persons aged 18 to 65 years: 76 patients with primary arterial hypertension and 20 healthy individuals (control group). Blood pressure was measured in all individuals using the office and ambulatory blood pressure mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Nonetheless, based on available literature regarding patients with hypertension without CSC, we may speculate that cytokines that were shown to be elevated in our study are also elevated in the general population of patients with hypertension. The cytokines IL‐6 (Zhang et al 2012), IL‐8 (Marek‐Trzonkowska et al 2015) and TNF‐α (Puszkarska et al 2019) are considered to play an important role in the pathogenesis of hypertension, but their excessive levels were also reported to negatively affect the function of numerous organs. Chae et al (2001) reported increased blood pressure as a stimulus for inflammatory response and hypothesized this to be a mechanism underlying the role of hypertension as a risk factor for atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, based on available literature regarding patients with hypertension without CSC, we may speculate that cytokines that were shown to be elevated in our study are also elevated in the general population of patients with hypertension. The cytokines IL‐6 (Zhang et al 2012), IL‐8 (Marek‐Trzonkowska et al 2015) and TNF‐α (Puszkarska et al 2019) are considered to play an important role in the pathogenesis of hypertension, but their excessive levels were also reported to negatively affect the function of numerous organs. Chae et al (2001) reported increased blood pressure as a stimulus for inflammatory response and hypothesized this to be a mechanism underlying the role of hypertension as a risk factor for atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cytokines may play an important role in modulating excitatory signaling pathways in the hypothalamus contributing to AngII-mediated hypertension. In particular, the proinflammatory mediator tumor necrosis factor a (TNFa) has been implicated in autonomic processes, including the development of hypertension in species as diverse as mice (Sriramula et al, 2008) and humans (Puszkarska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] IL-5, IL-6, and IL-12 levels correlated with mean choroidal thickness in aCSC while IL-6, IL-8, and tumor necrosis factor-alpha plasma levels correlated with hypertension in cCSC. [ 31 56 57 ] IL-6 and VEGF alter the junctional integrity of RPE and downregulate occludin and zonula occludens-1. Therefore, the authors speculated that increased levels of pro-inflammatory cytokines could lead to abnormal endothelium-dependent vasodilation, increased vascular permeability, and angiogenesis, which all have been found to be characteristic of CSC.…”
Section: Immune Mechanisms In Central Serous Chorioretinopathymentioning
confidence: 99%